Characterization of MtfA, a Novel Regulatory Output Signal Protein of the Glucose-Phosphotransferase System in Escherichia coli K-12 - Göhler, Anna-Katharina (American Society for Microbiology, 2012)
The glucose-phosphotransferase system (PTS) in Escherichia coli K-12 is a complex sensory and regulatory system. In addition to its central role in glucose uptake, it informs other global regulatory networks about carbohydrate availability and the physiological status of the cell. The expression of the ptsG gene encoding the glucose-PTS transporter EIICB(Glc) is primarily regulated via the repressor Mlc, whose inactivation is glucose dependent. During transport of glucose and dephosphorylation of EIICB(Glc), Mlc binds to the B domain of the transporter, resulting in derepression of several Mlc-regulated genes. In addition, Mlc can also be inactivated by the cytoplasmic protein MtfA in a direct protein-protein interaction. In this study, we identified the binding site for Mlc in the carboxy-terminal region of MtfA by measuring the effect of mutated MtfAs on ptsG expression. In addition, we demonstrated the ability of MtfA to inactivate an Mlc super-repressor, which cannot be inactivated by EIICB(Glc), by using in vivo titration and gel shift assays. Finally, we characterized the proteolytic activity of purified MtfA by monitoring cleavage of amino 4-nitroanilide substrates and show Mlc's ability to enhance this activity. Based on our findings, we propose a model of MtfA as a glucose-regulated peptidase activated by cytoplasmic Mlc. Its activity may be necessary during the growth of cultures as they enter the stationary phase. This proteolytic activity of MtfA modulated by Mlc constitutes a newly identified PTS output signal that responds to changes in environmental conditions.